OP0170 Low Income Is Associated with Lower Functional Capacity and Higher Disease Burden in RA Patients Younger than 65. (15th July 2016) - Callhoff, J.; Albrecht, K.; Hoffmann, F.; Luque Ramos, A.; Zink, A.
Abstract : Background: Low socioeconomic status is known to be a risk factor for unfavourable outcomes in rheumatoid arthritis (RA). Objectives: The aim of this analysis was to assess the influence of low income on functional capacity and disease burden. Methods: Patients with a diagnosis of RA (ICD-10 codes M05 or M06) in at least two quarters in 2013 from a large statutory health insurance in Germany (Barmer GEK) were randomly selected, stratified by age (18–49/50–64/65–80), sex and diagnosis (M05/M06). They were contacted by mail and asked to complete a questionnaire regarding self-reported diagnosis (for validation of claims diagnosis), sociodemographics, health behaviour, impact of RA on employment, the RA Impact of Disease questionnaire (RAID, 0: no impact, 10: highest impact) and the physical function questionnaire FFbH (0: total impairment- 100: full function). General linear models were used to assess the association of income and other sociodemographic factors with the FFbH and the RAID. Results: Of the 6, 195 patients who were contacted, a total of 3, 212 completed the questionnaire and 2, 585 (80%) reported to have RA. Among those, 2, 406 patients reported their household income. 31% of these had a low (<1, 500 Euro), 54% a medium (1, 500–3, 200 Euro) and 15% a high (>3, 200 Euro) household income. Patients with a low income had a mean FFbH of 67 (standard deviation 23) and a mean RAID of 4.8 (2.3), patients with a medium income had a mean FFbH of 74 (22) and a RAID of 4.1 (2.3) and those with a high income had a mean FFbH of 83 (18) and a RAID of 3.5 (2.3). In patients <65 years (n=1353), FFbH and RAID differed between patients with low and medium/high income (table 1 ) while education and lifestyle (smoking, being stressed) were not associated, insufficient exercise was only associated with FFbH. This analysis was controlled for the following work-related parameters that were strongly associated with functional capacity and disease burden: being less efficient at work, being on sick leave >6 weeks, having applied for disability pension and fear of not being able to work until retirement. Conclusions: In patients with RA aged below 65, low income was strongly associated with higher disease burden und poorer function. The effect of income on function and overall disease burden remained after controlling for factors like considering or applying for disability pension, presenteism and absenteism. Acknowledgement: This study was funded by the German Federal Ministry of Education and Research (01EC1405). Disclosure of Interest: None declared